Christian doctrine of social protection and social responsibility of business - Lukin, Siarhei V. (Journal of the Belarusian State University. Economics, 2018)
The article examines the Old Testament and the New Testament representation of and patristic ideas on social protection and social responsibility, ways to the sustainable well-being of every member of society, modern Catholic doctrine of social responsibility of business, contemporary Orthodox authors’ view of this question, and the motives of socially responsible business in the modern market economy.
Keywords: Christian; social responsibility; market; corporate; private; Catholic; Orthodox